The makārah structures of the formula (af'al: he does) and its connotations in Surat (Yasin): Applied study - alzaadima, aimudalaluh muhamad alsanusii (Tobruk University Journal of Social and Human Sciences, 2022)
This study is an analytical (practical)، lexical، morphological، grammatical and contextual study for the structure of three repetitive verbs with the form (Afaal – Yufaal) in Surah Yaseen. This study deals with the morphological indication for the structure of the verbs that have been repeated more than once in Surah Yaseen. It also discusses lexical meaning، the pattern، the importance of repetition، the declaration of the context indication of the verbs. Furthermore، the importance of the repetition for the verbs that change in their meaning and indication according to their place in the Quranic context as well as the syntactical and grammatical indication according to the Quranic context are discussed. The finding of this study reveals that the verbs change in their indication according to the context of Quranics' verses and the formula of individual pattern is also change from one context to another.   It also reveals that the formula can change their tense indication in order to benefit the new tense in context.